Pengembangan Smarthome Untuk Pengendalian dan Pemantauan Tirai dan Jendela Berbasis Internet of Things dan Android - Ade Winarni; Danandjaya Saputra; Zulfachmi; Hendi Setiawan; Slamet Santoso (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
Smart homes have become a major trend in the development of modern household technology. One important aspect of a smart home is controlling and monitoring curtains and windows. This research aims to develop a smart system that allows users to control and monitor their curtains and windows through an IoT-based platform and Android application. Additionally, the system is designed to increase energy efficiency by optimizing the use of natural light and ventilation. Users can monitor the energy consumption of their blinds and windows, so they can take action to reduce excessive energy use. The results of this research show that a smarthome system for controlling and monitoring curtains and windows based on IoT and Android can increase comfort and energy efficiency in the household. With the integration of IoT technology and Android applications, users have better control over their home environment, creating a smarter and more sustainable home.